Sustainable Competitiveness of Red Onion through Collective Action of Farmers in West Sumatra - Silfia Silfia; Amelia R. Nicolas; Elfa Rahmi Fitri; Resa Yulita; Lady Chania (Journal of Applied Agricultural Science and Technology, 2025)
The competitiveness and sustainability of agriculture are closely related to small-scale farming efforts. This research contributes to the transformation of individual farmers into a collective for small-scale farm enterprises, which face constraints necessitating the development of synergies. This is particularly relevant for red onion farmers in the high plains of the Gumanti Valley, Western Sumatra. The research questions are: How do the community's strengths sustain competitiveness and sustainability? What strategies can be formulated to enhance these aspects for the red onion farming community? The study aims to explore the strengths of onion farmers' communities and strategies to reinforce them, thereby promoting sustainability and competitiveness. Conducted in the agricultural area of the Gumanti Valley district of Solok Province from 2019 to 2020, this descriptive research employs CEEI, SWOT, and QSPM methodologies. The findings indicate that the competitiveness and sustainability of the red onion business have improved, with increases observed in collective innovation, supply chain management, and access to economic resources and opportunities, leading to enhanced income accumulation and profit sharing.